2004
DOI: 10.1111/j.1085-9489.2004.09404.x
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes‐induced expression of activating transcription factor 3 in mouse primary sensory neurons

Abstract: Diabetic neuropathy (DN) is a complication of diabetes that affects the distal terminals of lengthy-projecting sensory axons. To determine whether diabetes-induced axonal degeneration induces gene expression similar to nerve injury, the expression of activating transcription factor 3 (ATF3) by primary sensory neurons was examined in an experimental mouse model of DN. Diabetes was induced using streptozotocin in C57BL/6 mice, and ATF3 expression in lumbar dorsal root ganglia was assessed at different time point… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
1
3

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 52 publications
(73 reference statements)
4
22
1
3
Order By: Relevance
“…DN was also examined in C57BL/6J mice following a single high dose of STZ ( Table 2) [30,47,[55][56][57][58][59]. Similar to the majority of reports in low dose STZ-treated mice, DN was examined following diabetes duration of 1-9 weeks.…”
Section: Mouse Models Of Dnmentioning
confidence: 97%
See 1 more Smart Citation
“…DN was also examined in C57BL/6J mice following a single high dose of STZ ( Table 2) [30,47,[55][56][57][58][59]. Similar to the majority of reports in low dose STZ-treated mice, DN was examined following diabetes duration of 1-9 weeks.…”
Section: Mouse Models Of Dnmentioning
confidence: 97%
“…Investigations of DN in this model by Wright and co-workers reveal decreased mechanical sensitivity at 8 and 9 weeks post STZtreatment with reduced IENF densities but no changes in thermal thresholds. Nerve conduction velocities were not measured ( Table 2) [30,[55][56][57]59]. Thus, while there is no doubt that the C57BL/6J mouse develops profound diabetes in response to single high dose STZ treatment, evidence of DN is again only described in short term diabetes.…”
Section: Mouse Models Of Dnmentioning
confidence: 99%
“…Despite overwhelming evidence indicating that ATF3 is a stressinducible gene in a variety of tissues and acts as a transcriptional repressor, the physiological consequences of Atf3 expression are not well understood. However, it was recently reported that Atf3 is expressed in primary sensory neurons of diabetic mice [24] and ATF3 is expressed in the islets of patients with type 1 or type 2 diabetes [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is appreciated that frank nerve injury will lead to a variety of changes in the biology of the dorsal root ganglion cells of the injured axon, such as, for example, an increase in the expression of DRG activation transcription factor-3. 166 In this regard, changes in DRG activation transcription factor-3 expression have been observed not only after nerve section and compression, but after chemical stimuli (paclitaxel 135 ), in diabetes, 167 and even in some peripheral chronic inflammatory syndromes as diverse as equine laminitis. 168 It is thus reasonable to expect that many of these chronic states may lead to changes in nerve function that lead to the encoding of a nociceptive signal.…”
Section: Resultsmentioning
confidence: 99%